Is Materialism a Consequence of Natural Science? - Mutschler, Hans-Dieter (Rocznik Filozoficzny Ignatianum, 2019)
Naturalism is neither a consequence nor a presupposition of natural science in a threefold way: (1) the principle of matter, (2) the principle of supervenience and (3) the principle of the causal closure of the world are metaphysical principles. They are true, if naturalism is true. So, if you are a naturalist, you should find reasons for your worldview which are independent from natural science. But it is hard to see how this could work.